The ignorance explosion : understanding industrial civilization - Lukasiewicz, J. (Carleton University Press, 1994)
The author reveals the darker side of Western society's adoption of, and adaptation to, modern technology. Despite his portrayal of an increasingly complex, artificial and dehumanized technological environment, Lukasiewicz writes with humour and humanism and makes an enlightening contribution to the habitually grim literature on this subject.